Ferroptosis induced by iron overload promotes fibrosis in ovarian endometriosis and is related to subpopulations of endometrial stromal cells - Zhang, Yanqin; Liu, Xinyu; Deng, Mengqi; Xu, Chunyu; Zhang, Yubo; Wu, Di; Tang, Fan; Yang, Ruiye; Miao, Jinwei (Frontiers in Pharmacology, 2022)
Endometriosis (EMs) is defined as the presence of tissue somewhat resembling endometrial glands and stroma outside the uterus; the retrograded endometrium grows in the peritoneal cavity and elicits fibrosis. Ferroptosis is a recently discovered form of programmed cell death, which is iron-dependent. The induction of ferroptosis has been found to participate in fibrosis. However, the relationship between EMs fibrosis and ferroptosis remains unknown. In this study, we confirmed that the iron content in ectopic stromal tissue in ovarian EMs is significantly increased. We explored the role of iron-induced ferroptosis in the pathogenesis of ovarian EMs fibrosis for the first time. We found that ferroptosis in ectopic tissues was significantly more enhanced than that in eutopic tissues. Furthermore, we performed in vivo drug screening and found that ferroptosis induced by ferric ammonium citrate (FAC) could aggravate fibrosis. To clarify the mechanism of this process, the stromal composition of human uterine endometrium and endometrial tissue was characterized. Fibroblast-specific protein-1 was used for fibroblasts, smooth muscle actin alpha for myofibroblasts, and platelet-derived growth factor receptor beta (CD140b) for mesenchymal stromal cells (MSCs). The results demonstrated that the percentage of myofibroblasts was higher and the portion of MSCs was lower in ectopic endometrial stroma than those in eutopic endometrium. Moreover, the proportion of MSCs decreased significantly and the percentage of myofibroblasts increased considerably after FAC treatment in vitro. However, disruption of intracellular iron levels or ferroptosis via chelation of intracellular iron deferoxamine mesylate or ferroptosis inhibitor ferrostatin-1 could reverse this process, indicating that iron-induced ferroptosis plays a vital in ovarian EMs fibrosis. Considering that iron accumulation can feed the Fenton reaction to generate unquenchable amounts of free radicals, causing ferroptosis and tissue damage and thereby contributing to fibrosis, we validated the underlying mechanism that excess iron can facilitate fibrotic responses. Collectively, these data provide evidence that supernumerary iron is a key regulator in promoting MSCs ferroptosis and inducing ovarian EMs fibrosis.